Advertising Targeted to Children on Russian Market - Marchenko, Elizaveta (2020)
This thesis deals with the attitude of Russian parents to the advertisement from a variety of marketing channels targeted to children. The main goal is to understand the difference in the influence of marketing on children’s consciousness in different age periods. Another aim is to determine parents’ attitude to promotions for kids. What is more, the paper discloses the role of cartoon characters, bloggers and the Russian government in that type of advertisement with the help of secondary and primary researches. All these players are integral in the socialization of kids. Indeed, another question about ethics is considered throughout the whole thesis as well as children are recognized as one of vulnerable groups of population. The analysis gained from the survey and the interviews with parents leads to the idea that advertisement influences on different ages of children variously, and every child requires the individual approach.